Websprachen.net : sprache und kommunikation im internet - Siever, Torsten; Schlobinski, Peter, 1954-; Runkehl, Jens (Linguistik - Impulse & Tendezen ;, 2005)
The central theme of the volume is the language use, communicative behavioral patterns, and media-specific developments in the central areas of language and communication in the Internet. In addition to descriptions, the volume also provides a prospective.